2009
DOI: 10.1002/chem.200900629
|View full text |Cite
|
Sign up to set email alerts
|

Heterospin Single‐Molecule Magnets Based on Terbium Ions and TCNQF4 Radicals: Interplay between Single‐Molecule Magnet and Phonon Bottleneck Phenomena Investigated by Dilution Studies

Abstract: A series of isostructural compounds with formula [M(TCNQF(4))(2)(H(2)O)(6)]TCNQF(4)3 H(2)O (M=Tb (1), Y (2), Y:Tb (74:26) (3), and Y:Tb (97:3) (4); TCNQF(4)= tetrafluorotetracyanoquinodimethane) were prepared and their magnetic properties investigated. Compounds 1, 3, and 4 show the beginning of a frequency-dependent out-of-phase ac signal, and decreasing intensity of the signal with decreased concentration of Tb(III) ions in the diluted samples is observed. No out-of-phase signal was observed for 2, an indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 91 publications
4
40
1
Order By: Relevance
“…Previous investigations have observed that exchange coupling can enhance SMM behavior in Ln complexes. 12,[32][33][34][35][36] Exchange coupling in Cp* 2 Yb(bipy) (3)…”
Section: Exchange Coupling In Lanthanide Single Molecule Magnets (1)mentioning
confidence: 99%
“…Previous investigations have observed that exchange coupling can enhance SMM behavior in Ln complexes. 12,[32][33][34][35][36] Exchange coupling in Cp* 2 Yb(bipy) (3)…”
Section: Exchange Coupling In Lanthanide Single Molecule Magnets (1)mentioning
confidence: 99%
“…As there is no information regarding the electrical conductivity of the systems, it is difficult to explain the positive Pr-Cu exchange effect. Amongst the compounds prepared with such types of ligands with Gd 3+ , Dy 3+ and Tb 3+ as the lanthanide counterpart, both the ferromagnetic and antiferromagnetic types of 3d-4f magnetic exchange interaction have been observed [15][16][17][18]. The nature of interaction depends on the environment of the metal ions and on the structural parameters.…”
Section: Resultsmentioning
confidence: 95%
“…The ac susceptibility measurements were also performed under 1 kOe applied magnetic field, which led to a shift in the out-of-phase signal to higher temperature ( Figure S1 in the Supporting Information) due to fast quantum tunneling suppressed by applying the magnetic field. [25] Unfortunately, the peak of the out-of-phase signal was not detected due to the temperature limitations of the low-temperature apparatus. The origin of slow relaxation of the magnetization is still under question, but the large anisotropy provided by the Dy III ions might play an important role in the phenomenon.…”
Section: Resultsmentioning
confidence: 97%